Traduire c’est produire - Cornelia Möser (Glad!)
The productivity of translation is exemplified in this article by an analysis of the French and German feminist gender debates. In the first part, gender in translation is examined in its connection to nationalism, more specifically at the example of the untranslatable. In the following, potentials of agency in translation are drawn from the analysis of the feminist gender debates that are discussed in this perspective. Feminist research turns out to be a particularly instructive site for understanding the productivity of translation, yet this productivity is not automatically liberatory.